Kajian Potensi Kumbang Penyerbuk (Elaeidobius kamerunikus Faust) dan Thrips Bunga Hawaii (Thrips hawaiiensis Morgan) sebagai Agens Polinator pada Tanaman Kelapa Sawit - Efendi, Siska (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Pollinating beetle (Elaeidobius kamerunikus Faust) and thrips hawaiiensis (Thrips hawaiiensis Morgan) are the main pollinators of oil palm. Elaeidobius kamerunikus was introduced from Cameroon in 1982 while Thrips hawaiiensis is a native pollinator that already exists in the ecosystem of oil palm plantations in Indonesia. The purpose of this study was to study the potential of Elaeidobius kamerunikus and Thrips hawaiiensis as pollinating agents in oil palm. This research was conducted in a plasma plantation belonging to the Agricultural Technology Assessment Agency (BPTP) in Nagari Gunung Medan, Sitiung District, Dharmasraya Regency, West Sumatra Province. The parameters used to measure the potential of insect pollinators are population abundance, frequency of visits, and fruit set and fruit grade values, as well as the yield of palm oil produced. Observation of abundance was carried out by directly observing the population of these insects on male flowers of oil palm that were in anthesis. The frequency of visits by Elaeidobius kamerunikus and Thrips hawaiiensis was carried out on receptive female oil palm flowers using the Fix Sample Method. Observations of the frequency of visits were carried out in the morning, afternoon and evening. Pollination effectiveness is done by looking at the value of fruit set and the grade of fruit produced. Based on the analysis of the observed data, it is known that the population abundance of Elaeidobius kamerunikus is higher than that of Thrips hawaiiensis. Likewise with the frequency of visits Elaeidobius kamerunikus visited the female oil palm flowers more often than Thrips hawaiiensis. Based on the time of observation, Elaeidobius kamerunikus visited more female oil palm flowers in the morning and afternoon, while in the afternoon the frequency of Thrips hawaiiensis visits was higher. The total fruit formed as a result of pollination of Thrips hawaiiensis was 793 consisting of 177 grade A, 145.5 grade B, and 472.50 grade C, while the fruit pollinated by Elaeidobius kamerunikus was less, namely 514.5 fruit consisting of 150 grade A, 125.5 grade B, and 239 grade C. The fruit set values produced by the two pollinator insects tested were low, namely 46.45% for Elaeidobius kamerunikus and 59.43 for Thrips hawaiiensis.